A systematic review and meta-analysis of active case finding for tuberculosis in India - Tushar Garg; Lelia H. Chaisson; Fahd Naufal; Adrienne E. Shapiro; Jonathan E. Golub (Elsevier, 2022)
Summary: Background: Active case finding (ACF) for tuberculosis (TB) is the cornerstone case-finding strategy in India's national TB policy. However, ACF strategies are highly diverse and pose implementation challenges in routine programming. We reviewed the literature to characterise ACF in India; assess the yield of ACF for different risk groups, screening locations, and screening criteria; and estimate losses to follow-up (LTFU) in screening and diagnosis. Methods: We searched PubMed, EMBASE, Scopus, and the Cochrane library to identify studies with ACF for TB in India from November 2010 to December 2020. We calculated 1) weighted mean number needed to screen (NNS) stratified by risk group, screening location, and screening strategy; and 2) the proportion of screening and pre-diagnostic LTFU. We assessed risk of bias using the AXIS tool for cross-sectional studies. Findings: Of 27,416 abstracts screened, we included 45 studies conducted in India. Most studies were from southern and western India and aimed to diagnose pulmonary TB at the primary health level in the public sector after screening. There was considerable heterogeneity in risk groups screened and ACF methodology across studies. Of the 17 risk groups identified, the lowest weighted mean NNS was seen in people with HIV (21, range 3-89, n=5), tribal populations (50, range 40-286, n=3), household contacts of people with TB (50, range 3-undefined, n=12), people with diabetes (65, range 21-undefined, n=3), and rural populations (131, range 23-737, n=5). ACF at facility-based screening (60, range 3-undefined, n=19) had lower weighted mean NNS than at other screening locations. Using the WHO symptom screen (135, 3-undefined, n=20) had lower weighted mean NNS than using criteria of abnormal chest x-ray or any symptom. Median screening and pre-diagnosis loss-to-follow-up was 6% (IQR 4.1%, 11.3%, range 0-32.5%, n=12) and 9.5% (IQR 2.4%, 34.4%, range 0-86.9%, n=27), respectively. Interpretation: For ACF to be impactful in India, its design must be based on contextual understanding. The narrow evidence base available currently is insufficient for effectively targeting ACF programming in a large and diverse country. Achieving case-finding targets in India requires evidence-based ACF implementation. Funding: WHO Global TB Programme.